Management of public enterprises (with special reference to India). - "Chatterjee, S.K." (Delhi, 1982)
This book contains following topics: Why public sector?; Public Sector versus Private Sector; Constitutional Framework for state Regulation of Industries in India; Growth of Public Sector Concept in India; Forms of Public sector organisation; Boards of Management of Public Enterprises; Principles of Effective Management; Motivation in Mangement; The Profile of a Manager; Decision making in a public Enterprise; Personnel Management in the Public Sector; Management Development in the Public sector; Financial Management of Public Enterprises; Advertisement Needs of the Public enterprises; Public Utililties; Social Responsibilities of the Public sector; Management of Import Substitution; Public Sector Export Management etc.
Keywords: Government business enterprises management